Potensi Puding Ikan Toman (Channa micropeltes) dan Ikan Gabus (Channa striata) untuk Percepatan Penyembuhan pada Hewan Uji Tikus - Firlianty, Firlianty; Pratasik, Silvester B. (Sekolah Tinggi Ilmu Pertanian Wuna, 2018)
Everyone has different activities with different risks and often gets injured. Since wound healing process takes time, better handling and alternative medicinal administration are needed to accelerate the health recovery from trauma caused either by sharp or hard materials. Fish are high nutritive food enriched with minerals, fat, and protein. This study was intended to know the effect of snakehead fish extract on the healing process of white rat (Rattus novergicus). It applied an experimental method with 3 treatments. Results showed that fish pudding added with the snakehead fish extract gave good effect on the acceleration of wound healing process in the white rat.